Design of a Data Mart for Optimizing Product Sales Analysis at PT. X - Velline Samantha; Jap Tji Beng; Dedi Trisnawarman; Sri Tiatri; Tasya Mulia Salsabila; Fasia Meta Sefira; Tiara Zahro; Sania Alikha Rahmadira Latupono (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
With the advancement of technology, companies can now efficiently manage and analyze their data, providing valuable insights that support better business decisions. PT. X is one such company that wants to leverage this capability to optimize its sales data analysis. Therefore, the goal of this study is to design an effective data mart. During the development process, we used Kimbal's Nine-Step Methodology alongside the ETL (extract, transform, load) process to ensure the data was accurately extracted, transformed, and loaded into the data mart. The outcome of this research is a data mart and star schema tailored to PT. X specific needs. Testing results showed that query execution time increased by 40% and data accuracy improved by 80%. Report generation time was also optimized, resulting in a process that was 83% faster. These results demonstrate how a well-structured data mart can improve decision-making efficiency and data reliability.